Perbandingan Nilai EMP Pada MKJI 1997 Dengan EMP Lapangan Menggunakan Metode Regresi Linier (Studi Kasus: Jalan Letjen S Parman Kota Sidoarjo) - Dias Perdana, Romi; Junita Koesoemawati, Rr. Dewi; Kriswardhana, Willy (Journal of Applied Civil Engineering and Infrastructure Technology, 2022)
Traffic flow is expressed in passenger car units ( PCU) using a conversion favtor called the passenger car equivalent (PCE). The EMP value is used to overcome differences in the space required by a vehicle when making movements in traffic. The emp value is highly dependent on environmental factors, type of vehicle, terrain conditions, vehicle dimensions, the area of ​​road space used, and vehicle flow. This research was conducted to obtain a comparison of the value of EMP with MKJI 1997 with multyple linear regression calculations. Data collection is carried out to obtain traffic volume and road geometric. The analysis method used is using multyple linear regression method, the results of the analysis of the EMP value of the Letjen S Parman road were obtained for Jalan Letjen S Parman on the left side of weekdays 0.271 for MC and 2.581 for HV, for the right side of weekdays 0.244 for MC and 5.467 for HV, Letjen S Parman left side weekend 0.389 for MC and 2.495 for HV. There is a difference between the EMP value in the field and the emp value in MKJI, namely for MC of 7.74%, - 2.45%, 35.73%, and for HV of 53.50%, 78.05%, 51.90%.